Influence of temperature and pressure on quartz–water–CO2 contact angle and CO2–water interfacial tension - Sarmadivaleh, Mohammad; Al'Yaseri, A.; Iglauer, Stefan (Academic Press, 2015)
We measured water–CO2 contact angles on a smooth quartz surface (RMS surface roughness ~40 nm) as a function of pressure and temperature. The advancing water contact angle θ was 0° at 0.1 MPa CO2 pressure and all temperatures tested (296–343 K); θ increased significantly with increasing pressure and temperature (θ = 35° at 296 K and θ = 56° at 343 K at 20 MPa). A larger θ implies less structural and residual trapping and thus lower CO2 storage capacities at higher pressures and temperatures. Furthermore we did not identify any significant influence of CO2–water equilibration on θ. Moreover, we measured the CO2–water interfacial tension γ and found that γ strongly decreased with increasing pressure up to ~10 MPa, and then decreased with a smaller slope with further increasing pressure. γ also increased with increasing temperature.